Attitudes of Nonpalliative Care Nurses towards Palliative Care. (21st January 2015) - Tait, Victoria; Higgs, Megan; Magann, Linda; Dixon, Joanne; Davis, Jan Maree; Fernandez, Ritin
Abstract : The quality of palliative care given to terminally ill patients and their family members can be directly impacted by the attitudes that nurses hold towards palliative care. This study aimed to investigate the attitudes of nonpalliative care nurses towards death and dying in the context of palliative care. Nurses working within the medical aged care, cardiology and respiratory wards at two metropolitan teaching hospitals in Sydney completed the Frommelt Attitudes Towards Care of the Dying (FATCOD) scale, an anonymous self-administered questionnaire, and a twelve-item demographic questionnaire. A total of 95 completed surveys were used in the final analysis. The total FATCOD score was119.8 ± 11.1, patient FATCOD was79.6 ± 8.6, and family FATCOD was40.2 ± 4.4 . Of significance, the professional variables designation and role were associated with attitudes in the total FATCOD and country of birth, designation, highest level of education, and role were associated with attitudes towards the patient FATCOD. Scores for communication between the nurse and the terminally ill patient were poor. Health care facilities should focus on developing strategies to improve the communication skills among nonpalliative care nurses in order to optimize patient outcomes.